(untitled) (UMA Journal of Religious Studies, 2024)
Abstract The quest for God (good) amidst evil in the world has long been a puzzle to the human mind. If God exists and is infinite good and powerful and that this world was actually created by him, then it is difficult to understand why there could be so much evil in it. The notion of evil generally in African culture and religion is understood as a misfortune in human history. Evil can be caused by unseen phenomena. It can be caused by the gods that are offended by man’s deeds, or God taken vengeance for abomination committed by the community or an individual. Evil in Igala perspective can be classified under; moral, natural, physical and metaphysical evil. Igala and other cultural societies view evil to be caused by God who is all-powerful, all-knowing and all-benevolent. Thus, man holds God responsible for his mistakes and others of his wrong willful acts. From history, man as we read from the Bible is known for seeking a “safe ground” for himself (Free-will). This paper admonishes people in this 21st century to be ready to take responsibility of their evil deeds themselves and to others as the study focuses on how to eradicate evil from the society. The recommendations of this research discusses evil as means to an end, an opportunity for charity service. The method used is historical and analytical. The study concludes that knowledge is the only means that can be used as tools of eradicating the problem of evil from the society and also can be termed as an innovation in Igala religion and philosophy.